Korelasi Aksioma Etika Islam Dengan Perilaku Ekonomi Islam: Perspektif Syed Nawab Haider Naqvi - Shofiyah, Ziyadatus; Faishol, Muhammad (Universitas Muhammadiyah Jember, 2024)
This article aims to find out Syed Nawab Haider Naqvi's idea on the axioms of Islamic ethics and Islamic economic behavior. This research used library research methods with a descriptive approach. Syed Nawab Haider Naqvi is an economist in the contemporary era. The results of this research showed the ideas of Syed Nawab Haider Naqvi and the axioms of Islamic ethics towards the rules of Islamic economic behavior. Islamic ethical axioms, which include unity, equality, free will, and responsibility, The correlation between the axioms of Islamic ethics and Islamic economic behaviour is as follows: (1) The Axiom of unity, in Islamic economic behaviour must be in accordance with and not conflict with the principles of the Islamic religion. (2) The Axiom of Balance/Equality, in Islamic economic behaviour, the importance of achieving a balance between material and spiritual welfare. (3) Free will Axiom, in Islamic economic behaviour, the concept of human freedom is relative, means that it is in accordance with applicable Islamic ethical values. (4) Axiom of Responsibility, in Islamic Economic Behavior humans are given the responsibility to improve the quality of their economic and social environment.